The Effect of Promotion Through Instagram on Purchase Intention With E-Wom as an Intervening Variable in Men's Halal Skincare Products - Ibra Achmed Fauzy; Muhammad Sholahuddin (IQTISHADequity jurnal MANAJEMEN, 2023)
This study investigates the effect of promoting halal men's skincare products through Instagram on purchase interest, with e-WOM as a mediating variable. Using a quantitative research design, data were collected through questionnaires from 100 respondents who were Instagram users residing in Surakarta City. The study employed non-probability sampling with a purposive sampling technique. The results, analyzed using SEM-PLS with SMARTPLS 3.0 software, revealed that promoting through Instagram has a positive and significant impact on both e-WOM and purchase intention. Additionally, e-WOM was found to have a positive and significant influence on purchase intention and to mediate the relationship between promoting through Instagram and purchase intention. This study contributes to the existing literature by exploring the relationship between promoting through Instagram, e-WOM, and purchase intention in the context of halal men's skincare products. The findings suggest that promoting through Instagram is an effective marketing strategy for increasing purchase intention and generating positive e-WOM in this particular market segment. Moreover, the study highlights the importance of e-WOM as a mediating variable in the relationship between promoting through Instagram and purchase intention. These insights provide valuable implications for marketers and businesses seeking to enhance their social media marketing strategies and improve their sales performance.